THE EFFECT OF COMBINATION VEGETABLE TANNING MATERIALS AND SULPHITED OIL ON THE PHYSICAL PROPERTIES OF JACKET LEATHER - Heru Budi Susanto; Baskoro Ajie (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2022)
This research was aimed to determine the combination of vegetable tanning materials and Sulphited oil on the physical properties namely tensile strength, oil content, elongation, softness and shrinkage temperature and determine the factors that affect tensile strength, oil content, elongation, softness and shrinkage temperature leather tanning results. Raw hides/skins were processed up to acidification, pH was set to be 5 then tanned with the variation of vegetable tannin 15%, 17,5% and 20% respectively. Fatliquoring process used sulphited oil with variation of 12%, 15% and 18%. The jacket leather produced were tested using SNI 4593:2011. From this combination of treatment provided 9 (nine) treatment variation, each treatment was preformed triplicate. The results showed that the combination of vegetable tanning materials, 17.5% and 12% of sulphited oil was the result of variation in the optimum treatment for the leather to produce 208.29 N/mm2 tensile strength, oil content of 10.02%, 50.39% elongation and softness 5.13 mm and meets the requirements of SNI 4593: 2011 with the temperature shrinkage was at 79 oC. From the analysis of variance showed vegetable tanning material is the dominant factor affecting the tensile strength, oil conten and shringkage temperature. Sulphited oil is a factor that affects the oil content, elongation and softness.